Physical examination & health assessment - Camera, Ian M. (Mosby's nursing video skills, 2012)
Covers 15 body systems with detailed video demonstrations, critical thinking cases, and NCLEX-examination review questions and a QSEN-competencies checklist. Also includes state-of-the-art medical Archie animations and documentation exercise forms.